Unveiling the Gut Microbiome of Malaysia's Colobine Monkeys : Insights into Health and Evolution - Mohd Ridwan, Abd Rahman; Badrul Munir, Md Zain; Mohd Faudzir, Najmuddin; Nursyuhada, Othman; Hidayah, Haris; Nur Hartini, Sariyati; Ikki, Matsuda; Boon, Sook Yee; Yiling, Lee; Siew, Fen Lye; Muhammad Abu Bakar, Abdul-Latiff (John Wiley & Sons Ltd., 2024)
Colobines are primarily leaf- eating primates, depend on microbiota of gastrointestinal tracts for food digestion. However, the gut microbiota of Malaysia's colobines specifically langurs remains unstudied. Hence, we aim to analyze the fecal microbiomes of Malaysia's langurs using Presbytis femoralis, Presbytis robinsoni, Trachypithecus obscurus, and Trachypithecus cristatus from various landscapes as models. We collected samples from all four species across several areas in Peninsular Malaysia and performed 16S ribosomal RNA gene amplicon sequencing using the Illumina sequencing platform. Presbytis femoralis exhibited the highest bacterial diversity, followed by T. obscurus, T. cristatus, P. robinsoni and the lowest, P. siamensis. Over 11 million operational taxonomic units (OTUs) were identified across Malaysia's langurs spanning 26 phyla, 180 families, and 329 genera of microbes. The OTUs were dominated by Firmicutes, Proteobacteria, and Bacteroidetes. There are 11 genera of pathogenic bacteria were identified across all host species. Nine pathogenic bacterial genera inhabit both T. obscurus, indicating poor health due to low bacterial diversity and heightened pathogenicity. In contrast, P. robinsoni with the fewest pathogenic species is deemed the healthiest among Malaysia's langurs. This study demonstrates that alterations in diet, behavior, and habitat affect bacterial diversity in Malaysia's langurs' gut microbiota. Even though this is the first comprehensive analysis of langur microbiomes in Malaysia, it is important to note the limitations regarding the number of samples, populations sampled, and the geographical origins and landscapes of these populations. Our results suggest that Malaysia's langurs may harbor pathogenic bacteria, potentially posing a risk of transmission to humans.